Macronutrient and Calcium Composition with Substitution of Snakehead Fish (Channa striata) Flour as a Healthy Snack to Improve Children's Nutritional Status - Avrilia Anggraeni Pakereng; Dylla Hanggaeni Dyah Puspaningrum; Komang Windayani; Ida Bagus Agung Yogeswara (LPPM Universitas Dhyana Pura, 2026)
Nutritional concerns for children aged 1–9 years remain a priority, particularly regarding the fulfillment of energy, protein, and calcium requirements. The development of nastar as a snack made from snakehead fish flour is an effort to address these issues. The objective of this study was to determine the macronutrient and calcium content of the product and its contribution to children’s energy and nutritional adequacy. The study design employed a Completely Randomized Design (CRD) with six formulations of catfish flour supplementation: F0 (0%), F1 (10%), F2 (20%), F3 (30%), F4 (40%), and F5 (50%), each with three replicates. Tests for macronutrients (carbohydrates, protein, fat), calcium, and acceptability were conducted by 25 panelists based on the parameters of aroma, taste, texture, and color. Data analysis used a One-Way ANOVA test and Duncan’s multiple range test at a 5% significance level. The results showed that the substitution of snakehead fish meal had a significant effect (p<0.05) on the levels of carbohydrates, fat, and calcium. Preference tests on F1 (10%) and F2 (20%) were preferred by the panelists compared to the other formulations. F1 contained carbohydrates (72.27 g), protein (0.11 g), fat (15.65 g), and calcium (17.15 mg). F2 contains carbohydrates (66.7 g), protein (0.11 g), fat (20.05 g), and calcium (29.87 mg). F1 provides 10–15% (172.16 kcal) of the RDA for children aged 10–3 years, and F2 provides 10–15% (179.12 kcal) of the RDA for children aged 4–9 years, with a serving size of 40 g.